1994
DOI: 10.1103/physrevlett.73.2879
|View full text |Cite
|
Sign up to set email alerts
|

Young's Modulus of Two-Dimensional Ice from the Electrostatic Compression of Mercury/Water/Mercury Tunnel Junctions

Abstract: Solid-water films thinner than 0.8 nrn were confined between the mercury surfaces of a squeezable tunnel junction at 265~3 K. Uniaxial compression of the films was performed electrostatically by changing the junction bias. Mean compressive displacements were calculated from the nonlinear current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…36 Experimental support for such a phenomenon comes from studies using a mercury/water/ mercury tunnel junction at Tϭ265 K, where it was found that the Young's modulus of two-dimensional ice shows a maximum value ͑of ϳ20% of bulk ice I h ) as H was increased from 0.50 to 0.80 nm. 51 Particles under confinement exhibit large oscillations in the density as a function of H that span transitions between consecutive number of layers. Since the ordinary ice, I h , is sensitive to density ͑e.g., melting can be observed upon increasing the density͒, the alternation of water and ice phases as a function of H in confined geometries can be understood in these terms.…”
Section: •10mentioning
confidence: 99%
“…36 Experimental support for such a phenomenon comes from studies using a mercury/water/ mercury tunnel junction at Tϭ265 K, where it was found that the Young's modulus of two-dimensional ice shows a maximum value ͑of ϳ20% of bulk ice I h ) as H was increased from 0.50 to 0.80 nm. 51 Particles under confinement exhibit large oscillations in the density as a function of H that span transitions between consecutive number of layers. Since the ordinary ice, I h , is sensitive to density ͑e.g., melting can be observed upon increasing the density͒, the alternation of water and ice phases as a function of H in confined geometries can be understood in these terms.…”
Section: •10mentioning
confidence: 99%
“…in a thin nanoscale layer. Both experiments [4,5] and computer simulations [6][7][8] of thin layers of water reveal the transitions between various liquid, amorphous and crystalline phases of water and ice not found in the bulk.…”
Section: Introductionmentioning
confidence: 96%
“…When confined in nanopores the properties of water can be dramatically different from their bulk counterpart. For example, Porter and ZinnWarner [1] have reported that Young's modulus of solidwater thin films reaches its maximum value of ϳ20% of the bulk value as increasing film thickness from 0.5 to 0.8 nm, implying the possibility of confinement-driven order-disorder phase transition. However, the phase behavior of water confined in nanopores remains largely unexplored.…”
mentioning
confidence: 99%
“…We also confirmed that the solid phase that occurs under the lower loads (50 and 150 MPa) has the same crystalline structure. It appears that the structure of this bilayer ice crystal resembles none of the structures of existing ice polymorphs nor those of ices found in metallic or hydrophilic pores [1,[14][15][16][17]. The top view of the bilayer [ Fig.…”
mentioning
confidence: 99%